Truly Integrated Care Centred on the Individual: My Personal Vision for Wales - Morgan, Gareth P (Archives of Community Medicine and Public Health, 2016)
This paper offers my personal vision of truly integrated health and social care centred on the individual for Wales. This vision of an integrated health and social care system is simple - a seamless and efficient service. Wales in particular has a strong opportunity to develop a truly integrated health and social care system with the following key elements. A) Shared language B) Build and expand your evidence-base C) Clarity of purpose D) Be realistic and embrace change E) Keep learning and challenging data F) Policy and service effectiveness. How do we measure the effectiveness and impact? The answer is simple and concise – we use every metric available.